Cibergraça : fé, evangelização e comunhão nos tempos da rede - Silva , Aline Amaro da (2015)
This dissertation examines the effects of the invention of the internet in theology and society, defining what is cybertheology to find out what their contribution to better understand and interrelate culture, faith and the contemporary human being. Wraps up the theme in cybergrace, understood as the communion of persons in the network times. First, seize up cyberspace as a profoundly anthropological place where you can reflect theologically. The study also aims to verify how the network affects or enhances the relationship of communion between people, especially youth, predominant public in cyberspace. Furthermore, it analyzes the ecclesiological value of the internet in the mission of evangelizing all people, building the relationship between evangelization and communion in the digital age. The work uses basically the methods of exploratory, bibliographical and documental research. The dissertation is based mainly in books and articles by Antonio Spadaro, author of the book and the theological field "Cybertheology" background of this study. In support of sociological and cybercultural analysis of the first chapter, makes use of authors such as Manuel Castells, Pierre Lévy and André Lemos. In Trinitarian theology highlights the contribution of Gisbert Greshake and John Zizioulas. Also the work is inspired by scientific and theological thought of Teilhard de Chardin either directly or indirectly through authors such as Jennifer Cobb, with her work "Cybergrace".